Light Irradiation Coupled with Exogenous Metal Ions to Enhance Exopolysaccharide Synthesis from Agaricus sinodeliciosus ZJU-TP-08 in Liquid Fermentation - Hongyun Lu (MDPI AG, 2021)
To promote Agaricus sinodeliciosus var. Chaidam ZJU-TP-08 growth and metabolites accumulation, a novel integrated strategy was developed by adopting high levels of metal ions coupled with light treatment. The results revealed that yellow and blue light could significantly promote biomass and exopolysaccharides production, respectively. Furthermore, the yellow–blue light shift strategy could stimulate exopolysaccharides formation. Ca2+ ions coupled with blue light mostly promoted exopolysaccharides production related to oxidative stress, which was 42.00% and 58.26% higher than that of Ca2+ ions coupled with the non-light and dark cultivation without Ca2+ ions in 5-L bioreactor. RNA-seq was performed to uncover the underlined molecular mechanism regulated by light-induced gene expressions in exopolysaccharides biosynthesis and oxidative stress. The findings of this work provide valuable insights into adopting metal ions coupled with the light-assisted method for the macrofungus submerged fermentation for exopolysaccharides production.